PENGARUH MICROTRANSACTION YANG DISEBABKAN OLEH KECANDUAN DAN BERDAMPAK PERILAKU PEMBELIAN (Studi Kasus Pada Game Mobile Legend di Kota Jawa Tengah) - Mohammad Raditya Syahmaulana; Farida Indriani (Diponegoro Journal of Management, 2022)
Along with the development of technology, games are now a place of entertainment and earning a living. Because game enthusiasts have increased, this has resulted in a game revolution that is online, and online games have started to appear. Game developers are starting to look for ways to get the maximum profit in the game, that's why the term microtransaction emerged. Microtransaction is the purchase of virtual goods in the game using real money. One of the successful game developers in packaging their games is mobile legend. Mobile legend has succeeded in selling virtual products, increasing users every year, and having international competitions every year. This study proves that addiction can increase the desire to buy mobile legend games, even though loyalty cannot mediate the user's desire to make a purchase. The number of samples used in this study was 120 respondents with the condition that they had used or had not used mobile legend games, had lived in Central Java, had done microtransactions in mobile legend games. Quantitative data will be implemented using the SmartPLS application as a data processing tool. The results in this study indicate two answers, namely positive and negative. Positive on the influence of addiction that causes the desire to buy and negative on the mediation, namely the influence of loyalty on the desire to buy